EXTERNAL DEBT POSITION OF THE CENTRAL ASIAN COUNTRIES: A RETROSPECTIVE AND COMPARATIVE ANALYSIS - HASANOV, Munim (CENTRAL ASIA AND THE CAUCASUS, 2012)
The national economy of each of the Central Asian countries aims to create conditions that ensure a satisfactory standard of living for its population, to the extent available resources allow, based on sustainable development. According to its landmark definition, sustainable development is “development that meets the needs of the present without compromising the ability of future generations to meet their own needs” (italics mine. —M.H.).1 In other words, future generations should not have to pay for the counter-productive economic and other activity of the present generation. Here it is worth noting that external debt burden is among the factors that have a detrimental impact on such vitally important A review and analysis of the sources shows that, in the past, researchers in the Central Asian countries essentially ignored the problem of ex-ternal debt and did not offer methods to resolve it. There are very few analytical publications on this subject, while the media provides only sparse coverage of external debt. The reasons for this situation are as follows:(1) this problem is relatively new; it did not emerge until the Central Asian countries declared their independence in 1991.(2) before the beginning of the 2000s, it was very difficult or practically impossible to obtain reliable information on the external debt stock of the Central Asian countries, including from internal sources.(3) analysts and researchers were loath to deal with this problem, since public discussion of it was not encouraged.